Optimal attitude determination method in presence of noise and bias on different star sensors - Moghtadaei Rad, Amir (International Journal of Engineering and Technology, 2014)
There are different attitude determination methods which have been used in satellite and spacecraft by star tracker. Each of these methods have its own advantages and disadvantages depending on their application, stochastic characteristic of noise on sensors (bias or noise), and weight of noise falling on different sensors. The present study has thus explored the major methods from two perspectives: the effect of input noise or bias on each star sensor and the corresponding weight of each noise or bias falling on each sensor. These aspects are compared in each method and the optimal method according to each condition is introduced. N Vector, Triad, Quest, Q method and least square method are the methods studied and simulated in this article. Finally, a comparison is made between the methods and the optimal method is introduced theoretically and practically.